2017
DOI: 10.1111/pace.13104
|View full text |Cite
|
Sign up to set email alerts
|

Stricter criteria for left bundle branch block diagnosis do not improve response to CRT

Abstract: Stricter definition of LBBB did not improve response to CRT in comparison to the current AHA definition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
1
18
2
Order By: Relevance
“…Balloonocclusive contrast angiography of the coronary sinus tributaries is therefore recommended to guide electrode positioning. 16 Tester et al 7 reported for the same amount of contrast lower incidence; however, differently from us, they considered the increase of Creatinine ≥48 h and not within. Iodinated contrast causes direct cellular injury to kidney tubular cells that undergo swelling, blebbing, and apoptosis 12 resulting in contrast nephropathy.…”
Section: Contrast-induced Nephropathy and Cardiac Resynchronization Tmentioning
confidence: 63%
See 1 more Smart Citation
“…Balloonocclusive contrast angiography of the coronary sinus tributaries is therefore recommended to guide electrode positioning. 16 Tester et al 7 reported for the same amount of contrast lower incidence; however, differently from us, they considered the increase of Creatinine ≥48 h and not within. Iodinated contrast causes direct cellular injury to kidney tubular cells that undergo swelling, blebbing, and apoptosis 12 resulting in contrast nephropathy.…”
Section: Contrast-induced Nephropathy and Cardiac Resynchronization Tmentioning
confidence: 63%
“…3 However, up to 30-60% 4 of them do not benefit from this therapy, and so far, many efforts have been done to find the determinants of this lack of response to CRT, which are related [5][6][7][8] to either patients' and procedural characteristics and in addition to the post-procedural management. Furthermore, CRT improves symptoms, quality of life, and prolongs survival in patients with interventricular conduction delay (QRS complex width > 130 ms), LV ejection fraction (EF) ≤ 35%, and New York Heart Association (NYHA) Class II-IV symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…This might be interpreted as meaning that four slurred/notched leads are necessary to diagnose LBBB. However, interpretations present in the literature include the need for one notch/slur (Bertaglia et al, ), the need for three notched/slurred leads (Strauss, ), and a nonobligatory notch/slur (Perrotta et al, ; Zareba et al, ). In the current study, the presence of at least one lead with a notch/slur was deemed sufficient to fulfill the WHO/AHA definition criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were seen in the only other study that compared mortality in patients with LBBB according to the Strauss and conventional definitions, a retrospective study involving 111 patients (Mascioli et al, ). Moreover, patients with Strauss‐defined LBBB had a better echocardiographic response to CRT than patients with conventionally defined LBBB (Tian et al, ), although not those with WHO/AHA defined LBBB (Bertaglia et al, ). The latter finding was similar to our results showing the smallest difference in long‐term mortality between these two definitions, a finding that may be due to both definitions requiring a QRS notch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation